CMOS quasi‐digital temperature sensor for battery operated systems. Issue 21 (1st October 2013) - Azcona, C.; Calvo, B.; Medrano, N.; Celma, S.
Abstract : A high performance 1.2 V–0.18 µm CMOS quasi‐digital temperature sensor is presented with frequency output suitable to be used in battery operated systems. It is based on a multivibrator current‐to‐frequency converter and works properly over a temperature range of –40 to + 120°C, exhibiting a linear sensitivity of 442 Hz/°C with accuracy better than 1.0°C and a power consumption of 1.8 µW.